Young Workers' Perceptions of the Benefits of BPJS Employment as a Social Protection Instrument - Yohansen S, Cennet; Lubis, Suvia Fahrani; Hasibuan, Yusnita Adwiah; Br Sebayang , Nurul Adha Afraihan (PT. Hafasy Dwi Nawasena, 2026)
The rapid growth of Indonesia’s digital economy has increased the number of online platform workers, predominantly young workers with secondary education. However, their understanding of labor rights and social security remains limited. This study aims to analyze young workers’ perceptions of the benefits of BPJS Ketenagakerjaan as a social protection instrument. A quantitative descriptive approach is used by utilizing secondary data from surveys as well as additional data. The findings reveal that workers’ comprehension of social security, labor regulations, and legal protection mechanisms is still low, influenced by education level, work experience, and interaction with digital platforms. Structural challenges such as unclear employment status, limited specific regulations, and the absence of written work contracts further increase their vulnerability to labor rights violations. These results emphasize the need to enhance legal and digital literacy and strengthen the roles of the government, platform companies, and worker organizations in improving social protection for online platform workers.